Hope and fear in the experience of suspense. Issue 6 (18th August 2022) - Madrigal, Robert; Bee, Colleen; Chen, Johnny
ABSTRACT: The topic of mixed emotions has received considerable attention in recent years. However, two limitations in this research are the lack of (a) theoretical prediction regarding the types of conditions likely to cause one emotion to yield to another, and (b) attention given to the moment-to-moment (MTM) experience of mixed emotions. Using the empirical context of competitive contests, the mixed emotions state of suspense was manipulated in a series of studies designed to address these shortcomings. The results indicate that the most appropriate emotion pair to describe suspense is hope and fear. In addition, we find that the juxtaposition of these two emotions over the temporal sequence relies on viewers' interpretation of observed events relative to a preferred outcome. The results indicate a prevalence of bipolarity between hope and fear at lower levels of suspense and bivariance at higher levels. Given a high-suspense episode, both hope and fear are activated; whereas when suspense is low, hope (fear) is ascendant and fear (hope) declines when it becomes obvious a preferred competitor will ultimately win (lose).